Phase Transformation, Twinning, and Detwinning of NiTi Shape-Memory Alloy Subject to a Shock Wave Based on Molecular-Dynamics Simulation - Wang, Man; Jiang, Shuyong; Zhang, Yanqiu (Materials, 2018)
Martensitic transformation, reverse martensitic transformation, twinning, and detwinning of equiatomic nickel–titanium shape-memory alloy (NiTi SMA) under the action of a shock wave are studied using a molecular-dynamics simulation. In the loading process of a shock wave, B2 austenite is transformed into B19′ martensite, whereas in the unloading process of the shock wave, B19′ martensite is transformed into B2 austenite. With repeated loading and unloading of the shock wave, martensitic transformation occurs along with twinning, but reverse martensitic transformation appears along with detwinning. The mechanisms for the twinning and detwinning of NiTi SMA subjected to a shock wave are revealed in order to lay the theoretical foundation to investigate the shape-memory effect and superelasticity.